Maslinic acid induces autophagy by down‐regulating HSPA8 in pancreatic cancer cells. (8th March 2018) - Tian, Ye; Xu, Huanli; Farooq, Ammad Ahmad; Nie, Baozeng; Chen, Xiaoliang; Su, Shuonan; Yuan, Ru; Qiao, Gan; Li, Cong; Li, Xiao; Liu, Xiaohui; Lin, Xiukun
Abstract : Maslinic acid (MA), a natural pentacyclictriterpene, displays cytotoxic activity on various types of cancer cells. However, its underlying mechanism is unclear. In this study, we assessed the effect of MA on autophagy of human pancreatic cancer cells, and the potential autophagic pathway was presented. MA inhibited the proliferation and induced autophagy of Panc‐28 cells by altering the expressions of autophagy related proteins. SDS‐PAGE analysis revealed that one protein band was significantly down‐regulated in cells treated with MA, and the band was identified as heat shock protein HSPA8 as analyzed using Western blot and MS, MS/MS approaches. HSPA8 knockdown could significantly inhibit cell viability and enhance the cytotoxic effects of MA, whereas HSPA8 overexpression was able to enhance cell viability, diminishing the effects of MA. Western blot analysis indicated that the effect of MA on the expression of autophagy related genes was increased significantly in cells treated with HSPA8 inhibitor VER‐155008, whereas HSPA8 inducer geranylgeranylacetone antagonized the effects of MA. Our study provides evidence that MA is able to induce of autophagy via down‐regulation of HSPA8 in Panc‐28 cells.